Culturally responsive teaching in gifted education : building cultural competence and serving diverse student populations - Fugate, C. Matthew; Behrens, Wendy A.; Boswell, Cecelia A., 1949-; Davis, Joy Lawson, 1953- (New York, NY : Routledge, 2021)
'Culturally Responsive Teaching in Gifted Education' is a professional learning tool for practitioners who are working to create more culturally responsive school and classroom environments for gifted and talented students from special populations, including those who are culturally, linguistically, and economically diverse'--
Includes bibliographical references.
Keywords: Gifted children -- Education -- United States; Culturally relevant pedagogy -- United States; Educational equalization -- United States